ANALYSIS OF SERVICE QUALITY AN EMPIRICAL STUDY OF CUSTOMER SATISFACTION IN INFORMATION AND TECHNOLOGY SERVICE COMPANIES - Perwitasari Maharani, Belia; Dana Santoso Saroso (Dinasti Publisher, 2020)
Internet nowadays is the main media to run business. HYP is internet providers for business to business (B2B) companies considers sales performance which plays a major role in company performance. Sales volume only reached around 50% of the target for less than 3 years. This study to analyze the effect of service quality on repurchase intention that represents sales performance through customer satisfaction as an important intermediate variable. The sample used in this study were 100 respondents. It used stratified sampling techniques and then the data is analyzed using path analysis and importance performance analysis (IPA). Based on the results found that indirectly the quality of service through customer satisfaction has a positive and significant effect on repurchase intention which is considered to represent sales performance. The improvement in service quality that must be done is to increase responsiveness to customer complaints and requests.